Preparation of Iron Oxide/Graphene Composites and Their Photocatalytic Properties for Methylene Blue Under Sunlight - Chen, Tao; Zhang, Feng-Jun; Wu, Zhao-Sheng; Jiang, Tao; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
Three kinds of iron oxide/graphene composites were prepared using three different ferric salts [FeCl3, Fe(NO3)3, FeSO4] to react with graphene oxide and followed by a heat treatment. Then, the structures of different iron oxide/graphene composites were compared and analyzed by IR spectra and scanning electron microscopy. After that the degradability using different iron oxide/ graphene composites to degrade methylene blue was explored by ultraviolet spectra. The results showed that iron/graphene (FeCl3 as iron source) composite has better degradability under sunlight than that of other iron/graphene composites (Fe(NO3)3 or FeSO4 as iron source).